An experimental and simulation study for hydrogen and short-chain alcohol along with diesel fuel on the CRDI engine behaviors - Upendra Rajak; Manoj Panchal; Ibham Veza; Tikendra Nath Verma; Ümit Ağbulut (International Journal of Thermofluids)
Hydrogen (H2) and ethanol (C2-type short-chain alcohol) mixtures are receiving significant interest as alternative fuel substitutes in diesel engines. This study numerical investigates the combined effects of using hydrogen and ethanol (at concentrations of 5 %, 10 %, and 15 %) blends on a diesel engine's performance, combustion, and emissions characteristics using diesel R-K software. The results showed that nearly all hydrogen blend enrichments consistently produced higher BTE than that of only ethanol-added test fuel. Hydrogen availability in the combustion chamber also lowered the specific fuel consumption. Concerning the combustion characteristics, compared to the base fuel, the hydrogen enrichment increased the maximum cylinder pressure, while the ethanol decreased it. Increasing the amount of hydrogen for all engine loads leads to an observed improvement in brake thermal efficiency by 16.1 % and cylinder pressure by 3.3 % for BF(basefuel)+10%H2compared to base fuel at full load. This is attributed to the enhanced mixture formation and greater flame speed of hydrogen. Higher engine loads, including 15 % hydrogen resulted in increased exhaust temperature, soot, and NOx due to higher in-cylinder temperature value. However, it also led to considerable reductions in specific fuel consumption emissions, PM emissions, and smoke emissions across all loads. This study achieved higher levels of PM emission reduction, reaching up to 15 % hydrogen content. Furthermore, introducing 15 % hydrogen resulted in a significant surge in NOx emissions.